Does Litigation Risk Shape Environmental Disclosure Decisions? Evidence from Peers’ Environmental Disclosure Lawsuits - Robinson, Scott A.; Skinner, A. Nicole; Wang, Jasmine (The Accounting Review, 2025)
ABSTRACT We examine how managers’ incentives to minimize litigation risk interact with the unique features of environmental information to shape disclosure decisions. We rely on peer firms’ lawsuits to generate variation in environmental disclosure litigation risk, consistent with prior research and anecdotal evidence suggesting that firms perceive an increase in environmental disclosure litigation risk after a peer firm is sued for related disclosures. Although we provide mixed evidence around changes in total environmental disclosure in response to peer lawsuits, we offer robust evidence that firms provide more forward-looking (and less historical) environmental disclosures in their conference calls in response to peers’ environmental disclosure lawsuits. Our evidence is consistent with firms providing less verifiable disclosures to minimize the risk of being sued for misrepresenting their environmental information. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: K22; M14; M41.